An employer's guide to managing professionals on the autism spectrum - Scheiner, Marcia; Bogden, Joan (Jessica Kingsley Publishers, 2017)
This is a comprehensive reference guide for managers and colleagues of people with Asperger's Syndrome (AS). Containing detailed descriptions of workplace behaviours, the underlying issues that cause them, and recommendations on how to manage them, this book will help managers and colleagues of people with AS manage behaviours in a respectful way.